Sistem Informasi Terpusat Kantor Desa Lonrong (SIMPULO) Berbasis Website - Nurul Febrianti. B; Nurwahid Sym Syam; Firkawati Firkawati (Journal of Innovative and Creativity (Joecy), 2026)
This study aims to: (1) develop a web-based Centralized Information System for the Lonrong Village Office (SIMPULO); (2) determine user responses to the web-based Centralized Information System for the Lonrong Village Office (SIMPULO). The method used in this study is the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The results of the study indicate that: (1) the existing system at the Lonrong Village Office is still manual and not well integrated. The population data recording process still uses separate Microsoft Excel files, and correspondence management is also carried out manually, resulting in delays, data duplication, and recording errors; (2) the web-based Centralized Information System for the Lonrong Village Office (SIMPULO) has been successfully designed using UML modeling, including use case diagrams, Activity diagram s, and database design to support centralized population data management and correspondence processing; (3) based on Black Box testing, all system functions operate as expected, and expert validation results show a validity level of 1, categorized as very high; (4) user responses to the system are very positive, with a score of 90.7%, indicating that the system is feasible to use and can be further developed.